MRI‐based transfer function determination for the assessment of implant safety - Tokaya, J.P.; Raaijmakers, A.J.E.; Luijten, P.R.; Bakker, J.F.; Berg, C.A.T. (Magnetic resonance in medicine, 2017)
Purpose We introduce a new MR‐based method to determine the transfer function (TF) for radiofrequency (RF) safety assessment of active implantable medical devices. Transfer functions are implant‐specific measures that relate the incident tangential electric field on an (elongated) implant to a scattered electric field at its tip. The proposed method allows for TF determination with a high spatial resolution in relatively fast measurements without requiring dedicated bench setups from MRI images. Theory and Methods The principle of reciprocity is used in conjunction with the potential to measure currents with MRI to determine TF. Low‐flip angle 3D dual gradient echo MRI data are acquired with an implant as transceive antenna, which requires minimal hardware adaptations. The implant‐specific TF is determined from the acquired MRI data, with two different postprocessing methods for comparison. Results TFs of linear and helical implants can be determined accurately (with a Pearson correlation coefficient R ≥ 0.7 between measurements and simulations, and a difference in field at the tip ΔEtip ≤ 19%) from relatively quick (t < 20 minutes) MRI acquisitions with (several) millimeter spatial resolution. Conclusion Transfer function determination with MRI for RF safety assessment of implantable medical devices is possible. The proposed MR‐based method allows for TF determination in more realistic exposure scenarios and solid media. Magn Reson Med 78:2449–2459, 2017. © 2017 International Society for Magnetic Resonance in Medicine